The effect of fatigue on trunk and pelvic jump-landing biomechanics in view of lower extremity loading: A systematic review - Stefan, V.; Camilla, D. B.; Cedric, D. B.; Özge, O. K.; Tine, W.; Jos, V.; Roosen, P.; Roel, D. R. (Journal of Human Kinetics, 2023)
Fatigue has often been considered a risk factor for developing sports injuries, modulating lower extremity jumplanding biomechanics. The impact of fatigue on proximal trunk and pelvic biomechanics has been suggested to play an important role in lower extremity loading and injury risk, yet the available evidence remains ambiguous as the trunk and pelvis were often not the primary focus of research. Therefore, the purpose of this systematic review was to determine how fatigue affects trunk and pelvic three-dimensional jump-landing biomechanics. PubMed (MEDLINE), Web of Science, Embase, CINAHL and SPORTDiscus were consulted up to and including April 2022 for potential studies investigating the effect of fatigue on trunk and pelvic kinematics, kinetics and/or muscular activity during jump-landing tasks in healthy, physically active populations. Methodological quality of the studies was assessed by the modified Downs and Black checklist. Twenty-one studies were included and methodological quality was moderate to high among these studies. The results indicate prevailing evidence for more trunk flexion during standardized jump-landing tasks after lower extremity muscle fatigue. Otherwise, lumbo-pelvic-hip muscle fatigue does not seem to elicit major detrimental changes to these jump-landing biomechanics. Although a wide variability of trunk and pelvic jump-landing strategies was observed, the results provide evidence for increased trunk flexion after lower extremity muscle fatigue. This proximal strategy is suggested to help unload fatigued lower extremity structures and lack of this compensation might increase knee injury risk